Wrocław - ośrodek szkolnictwa wyższego na Dolnym Śląsku - Potoczna, Iwona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The aim of the paper to evaluate of the state and the dynamics of the development of higher education in Wroclaw. It will be done according to the number of students (the system of studies, the type of schools and the specialization), graduates and academic personnel. The research that have been done confirm the significant role of Wroclaw as the center of higher education in Lower Silesia and in Poland. The analysis of the statistic data shows that the development of education in Wroclaw proves some kind of regularity adequate for the country. The analysis also emphasises the influence of varied conditions on present and future situation of higher education in the Lower Silesian Region. The statistics come from the year book 1996-2004. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 167-177